Universities, Public Research and Regional Innovation Output: An Empirical Study of 19 Technologies in Germany - Thomas Brenner; Charlotte Schlump (Philipps-University Marburg, Department of Geography, 2013)
It has been repeatedly shown that universities and public research institutes contribute to local innovation generation and facilitation. The mechanisms behind this contribution are well discussed in the literature. However, detailed empirical examinations are missing. We analyse the impact of universities and public research on regional innovation output. Thereby we analyse separately 19 technologies and distinguish whether university education and public research are rather innovation generators or innovation facilitators. All analyses are conducted on German data.
Keywords: C13; I25; O31; R12; 330; regional innovation systems; innovation output; university; public research